Preclinical data do not support the use of amiodarone or dronedarone as antiparasitic drugs for Chagas disease at the approved human dosing regimen - Francisco, Amanda F.; Chen, Gong; Wang, Wen; Sykes, Melissa L.; Escudié, Fanny; Scandale, Ivan; Olmo, Francisco; Shackleford, David M.; Zulfiqar, Bilal; Kratz, Jadel M.; Pham, Thao; Saunders, Jessica; et al. (Frontiers in Tropical Diseases, 2023)
The repurposing of approved drugs is an appealing method to fast-track the development of novel therapies for neglected diseases. Amiodarone and dronedarone, two approved antiarrhythmic agents, have been reported to have potential for the management of Chagas disease patients displaying symptomatic heart pathology. More recently, it has been suggested that both molecules not only have an antiarrhythmic effect, but also have trypanocidal activity against Trypanosoma cruzi, the causative agent of Chagas disease. In this work, we assessed the in vitro activity of these compounds against T. cruzi, the in vivo pharmacokinetics, and pharmacodynamics, to determine the potential for repurposing these drugs as therapies for Chagas disease. Based on these results, we were unable to reproduce the in vitro potencies of amiodarone and dronedarone described in the literature, and both drugs were found to be inactive or cytotoxic against a variety of different mammalian cell lines. The evaluation of in vivo efficacy in a bioluminescent murine model of T. cruzi did not show antiparasitic activity at the highest tolerated dose tested. While the potential of amiodarone and dronedarone as antiarrhythmic agents in Chagas cardiomyopathic patients cannot be completely excluded, a trypanocidal effect in patients treated with these two drugs appears unlikely.